Level of aurathrenomedullin in chronic heart failure of ischemic genesis: associations with clinical manifestations - E. I. Myasoedova (Бюллетень сибирской медицины, 2019)
Objective. To identify and evaluate the relationship between the level of proadrenomedullin and clinical and anamnestic data of patients with chronic heart failure of ischemic genesis.Materials and methods. 240 men with chronic forms of coronary heart disease (mean age 55.9 [43; 63] years) and past Q-forming myocardial infarction were examined. Of these, 110 patients had chronic heart failure and preserved left ventricular ejection fraction (group 1) and 130 patients had chronic heart failure and dilatation with a low left ventricular ejection fraction (group 2). In all patients the MR-proADM level in the blood serum was determined.Results. In the control group, the level of MR-proADM was 0.49 [0.18; 0.58] nmol /l. In the meantime, it was statistically significantly higher in the studied groups of patients than in the control group (p < 0.001 and p < 0.001, respectively). And in the group of patients with chronic heart failure and dilatation with a low left ventricular ejection fraction, it was statistically significantly higher than in the group of patients with chronic heart failure and preserved left ventricular ejection fraction (1.72 [1.56; 1.98] nmol/l and 0.89 [0.51; 1.35] nmol/l, respectively, p < 0.038). The study demonstrated the presence of statistically significant associations between the level of MR-proADM and the severity of chronic heart failure and exertional angina pectoris as well as between the presence of a constant form of atrial fibrillation and the levels of systolic and diastolic blood pressure.Conclusion. MR-proADM is a new promising marker, which will be possible to use as a diagnostic standard for assessing the effectiveness of treatment of cardiac patients.